On the relationship between satellite-retrieved surface temperature fronts and chlorophyll a in the western South Atlantic - Saraceno, M. (2005)
Fil:Saraceno, M. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.